ATLAS OF LOCAL SEISMIC CULTURES IN CHILE: IDENTIFICATION OF NATIVE EARTHEN-ARCHITECTURAL HERITAGE AND ITS VULNERABILITY TO GREATER RISKS - Suilan Hau Espinosa, María Inés; Richard Jarpa, Thomas Sebastien (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
This paper presents the background for the development of the Atlas of Local Seismic Cultures (LSC Atlas) project in Chile. The aim is to ind the tools to intervene and to protect vulnerable earthen-built heritage in Chile, as well as a methodology of analysis to recognize the legacy of traditional construction against earthquakes. Based on the premise of the existence of a seismic resistant construction logic, intrinsic to earthen architecture in seismic prone areas, the inluence of the frequency of seismic activity in a place is evaluated, a precedent that establishes the degree of preparedness, response and community resilience against disasters. The concept of LSC recognizes the existence of communities affected by different types and frequency of earthquakes. These have historically developed an appropriate and relevant constructive intelligence in a speciic location, creating a vernacular seismic resistant construction system. As a platform, the Atlas will permit the management of a database to geo-reference, collect and evaluate the establishment of LSC, by identifying the different technologies used in earthquake resistant earthen architecture, locating them in the territory, and analyzing their socio-cultural, economic and environmental settings. Based on this vernacular knowledge to devise emergency plans and intervention in earthen buildings, appropriate and relevant solutions to each locality will be put forward, leading to the generation of sustainable actions in time. In Chile, a developing country, it is common to suggest modern and highly sophisticated solutions, denying popular knowledge and their traditional aptitude towards seismic resistant building systems. Through the Chilean LSC Atlas the re-evaluation of the particular knowledge of each community, their intangible heritage and their “know-how” is performed. This form of intangible heritage provides a weal th of knowledge for trad itional seismic r esistant construction.